Simple TiO 2 Coatings by Sol–Gel Techniques Combined with Commercial TiO 2 Particles for Use in Heterogeneous Photocatalysis - Vera, Maria Laura (2017)
TiO2 coatings were obtained by a combination of a sol?gel process with the addition of commercial TiO2 particles (Degussa-Evonik P25). Simple and composite (with P25) sols were deposited by dip-coating on glass plates giving simple and composite coatings. The order of addition of reagents in the preparation of sols, the incorporation of P25 to the sols, and the thermal treatments were analyzed as variables to improve the photocatalytic activity. The samples were completely characterized with respect to the amount of deposited TiO2, the crystal structure (XRD) and the morphology (SEM). The activity of the supported photocatalysts (simple, composite and P25 coatings) was evaluated using 4-chlorophenol degradation and Cr(VI) reduction in the presence of EDTA as model photocatalytic systems. The stability of sols and the photocatalytic activity of the resulted coatings depended strongly on the order of addition of the reagents to obtain the simple sol. Sols prepared by adding the alcohol-water-HCl mixture to the precursor were the simple sols presenting a very good stability that permitted the incorporation of powdered P25 without the addition of additives. The composite coatings prepared from these simple sols were the most active in both photocatalytic systems and also presented the highest resistance to scratch.